Polarization of dental caries among individuals aged 15 to 18 years - Fernando Neves Hugo; Glauber Campos Vale; Renzo Alberto Ccahuana-Vásquez; Silvia Cypriano; Maria da Luz Rosário de Sousa (University of São Paulo, 2007)
OBJECTIVE: To evaluate the role of socioeconomic variables and self-perceived oral health in the polarization of caries among adolescents in Santa Bárbara D'Oeste, Brazil. MATERIAL AND METHODS: Cross-sectional study. Sampling was randomized and sample size was defined according to WHO criteria. Two hundred and seventy seven adolescents (15 to 18 year-old) were examined by five trained examiners that assessed DMFT index according to WHO criteria. Self-perceived oral health, access to dental services and socio-demographic variables were self-reported. Student's t tests, chi-square tests, and multivariate logistic regression (with significant caries index (SiC) as the outcome), were performed. RESULTS: Mean DMFT was 5.48 (±4.22) and the proportion of "caries free" subjects was 15.5%. Mean DMFT (9.71±2.85) and mean D (1.67±2.18) of SiC positive subjects were significantly higher than mean DMFT (2.88±2.17) and mean D (0.45±0.87) of SiC negative subjects (p<0.0001). Mean D of white (0.76±1.51) was significantly smaller than mean D of non-white subjects (1.32±2.01). The only variable independently associated with the "SiC positive" outcome was "report of toothache within six months prior to the study" [OR=1.83 (95%CI 1.08 to 3.12)], p<0.001. CONCLUSION: SiC was associated with "report of toothache" but not with socio-demographic variables in the studied population.